2011
DOI: 10.1097/aog.0b013e318215dd4e
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Discharge After Laparoscopic Hysterectomy

Abstract: Same-day discharge after laparoscopic hysterectomy is associated with low readmission rates and minimal emergency visits in the immediate postoperative period. Same-day discharge may be a safe option for healthy patients undergoing uncomplicated laparoscopic hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
71
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 8 publications
5
71
2
1
Order By: Relevance
“…[1][2][3][4] Our population-based study found that 30-day revisits for clinically significant surgical site infections following ambulatory operations accounted for less than 15% of all-cause revisits to inpatient or ambulatory surgery settings. 5 The reasons for other revisits and their relationship to the index operation are unknown.…”
mentioning
confidence: 99%
“…[1][2][3][4] Our population-based study found that 30-day revisits for clinically significant surgical site infections following ambulatory operations accounted for less than 15% of all-cause revisits to inpatient or ambulatory surgery settings. 5 The reasons for other revisits and their relationship to the index operation are unknown.…”
mentioning
confidence: 99%
“…Several investigators have demonstrated the feasibility and safety of same-day discharge following hysterectomy for benign diagnoses [10,14,15]. de Lapasse et al [13] documented that 97.1% of such patients could also be successfully discharged within 24 h of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Perron-Burdick et al [15] evaluated the potential for same-day discharge with 1,015 patients following treatment with laparoscopic hysterectomy. In their study, 52% of the patients (TLH = 240; supracervical hysterectomy = 287) were discharged on the same day of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations